A COMPARITIVE STUDY OF EXECUTIVE FUNCTIONS IN PATIENTS WITH EARLY AND LATE ONSET ALCOHOL DEPENDENCE - Aayush Srivastav; Priyanka Renita D'Souza; Bharath Reddy (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BACKGROUND: Regular alcohol consumption has been linked to notable structural and functional alterations in the brain, particularly in the prefrontal cortex and related networks, which ultimately lead to deficiencies in executive functioning (1,2) and need to be compared between individuals having early vs late onset alcohol dependence. AIM: To estimate and compare the executive functions among patients with early onset versus late onset alcohol dependence syndrome. METHODS: A cross-sectional observational study was carried out among randomly selected 60 participants who were diagnosed with alcohol dependence syndrome as per ICD-10(DCR) criteria, severity of alcohol dependence was assessed via Severity of alcohol dependence questionnaire(SADQ), executive functions assessed in the study included Attention which was assessed via Digit span test, concentration assessed via Serial subtraction test and working memory assessed via Rey auditory verbal learning test (RAVLT) and comparative analysis of executive functions between early and late onset alcohol dependence groups was done. RESULTS: A total of 60 participants 30 participants in each group were assessed and results compared that showed no significant association found between the onset of alcohol dependence and attention, as indicated by a Pearson Chi-Square value of 1.714 and a p-value of 0.19.There was no significant association found between the onset of alcohol dependence and concentration, as indicated by a Pearson Chi-Square value of 1.833 and a p-value of 0.4. The early-onset group achieved an average score of 6.1 on the RAVLT (Immediate recall), whereas the late-onset group had a slightly higher average score of 6.47. The p-value was 0.577, suggesting that there is no significant difference. The average scores for the RAVLT (Learning) were almost the same for both groups. The early-onset group scored 5.9, while the late-onset group scored 5.97. The p-value was 0.923, indicating that there is no significant difference.The early-onset group achieved an average score of 5.97 on the RAVLT (Forgetting), whereas the late-onset group obtained an average score of 6.13. The p-value was 0.826, suggesting that there is no significant difference. CONCLUSION: The executive functioning does not show significant differences depending on the age of onset. These findings underscore the significance of addressing alcohol use early on and emphasize the necessity of thorough cognitive evaluations and personalized rehabilitation programs for individuals with alcohol dependence, regardless of when it started.